Systematic errors in digital volume correlation due to the self-heating effect of a laboratory x-ray CT scanner. (15th March 2017) - Wang, B; Pan, B; Tao, R; Lubineau, G
Abstract: The use of digital volume correlation (DVC) in combination with a laboratory x-ray computed tomography (CT) for full-field internal 3D deformation measurement of opaque materials has flourished in recent years. During x-ray tomographic imaging, the heat generated by the x-ray tube changes the imaging geometry of x-ray scanner, and further introduces noticeable errors in DVC measurements. In this work, to provide practical guidance high-accuracy DVC measurement, the errors in displacements and strains measured by DVC due to the self-heating for effect of a commercially available x-ray scanner were experimentally investigated. The errors were characterized by performing simple rescan tests with different scan durations. The results indicate that the maximum strain errors associated with the self-heating of the x-ray scanner exceed 400 µε . Possible approaches for minimizing or correcting these displacement and strain errors are discussed. Finally, a series of translation and uniaxial compression tests were performed, in which strain errors were detected and then removed using pre-established artificial dilatational strain-time curve. Experimental results demonstrate the efficacy and accuracy of the proposed strain error correction approach.